Health-promoting behavior and its determinants towards non-communicable diseases among adult residents of the Gedeo zone, South Ethiopia: the application of the health belief model - Hareru, Habtamu Endashaw; Mamo, Tizalegn Tesfaye; Abebe, Mesfin; Debela, Berhanu Gidisa (Frontiers in Public Health, 2024)
Background Non-communicable diseases are becoming a challenge for the health care system in Ethiopia, which has suffered a double burden from infectious and rapidly increasing non-communicable diseases. However, there is little information on health-promoting behavior in the study settings. Thus, the purpose of this study was to determine health-promoting behaviors and its associated factors among adult's residents of Gedeo zone. Methods A cross-sectional study was conducted among 705 adult residents of Gedeo zone, south Ethiopia, selected using a multi-stage sampling technique. Interviews administered through a structured questionnaire were used to collect the data. The data were entered using Kobo Collect and analyzed using Stata version 17. The baseline characteristics of the participants were summarized using descriptive statistics. The independent sample t-test and one-way ANOVA were used to compare two groups and more than two groups, respectively. Stepwise multiple linear regression analysis was used to identify the potential determinants of health-promoting behavior and its components. Statistically significant factors were declared at p-value of less than or equal to 0.05. Results The overall means score for health-promoting behavior was 73.88 ± 16.79. Physical activity and spiritual growth had the lowest and highest mean scores, respectively. The variables: gender, marital status, education, family history of NCDs, health insurance status, perceived health status, knowledge of NCD risk factors, risk perception of NCDs, expected outcome, cues to action, and self-efficacy showed a statistically significant difference in overall health-promoting behavior. The total health-promoting behavior score was associated with age, gender, perceived health status, marital status, family history of NCDs, health insurance, knowledge of NCD risk factors, perceived threat, expected outcome, self-efficacy, and cues to action. Conclusion and recommendations In the study, the mean score of health-promoting behaviors was low. Socio-demographic and economic variables, family history of NCD, perceived health status, knowledge of NCD risk factors, perceived threat, expected outcome, self-efficacy, and cues to action affect health-promoting behaviors. Therefore, the study suggests establishing health promotion programs to increase residents' awareness of health-promoting lifestyles, empower them to adopt healthy lifestyles, and improve health outcomes by increasing self-efficacy, providing education, and creating supportive environments.